Inventory Accounting Method and Earnings‐Price Ratios* - DHALIWAL, DAN S.; GUENTHER, DAVID A.; TROMBLEY, MARK A. (Contemporary Accounting Research, 1999)
Abstract Lee (1988) finds that LIFO firms have higher earnings‐price (EP) ratios than non‐LIFO firms despite the income‐reducing effects of LIFO, a result contrary to economic intuition that Lee describes as a “puzzle.” This paper attempts to resolve this puzzle by introducing refined measures of variables that are related to both EP ratios and inventory costing method choices. The improved proxies are analysts' expectations of future growth rather than realized growth, beta computed using a procedure designed to reduce measurement error rather than the usual OLS beta, and leverage as a supplemental risk measure. Further, we control for expected earnings changes, since transitory earnings shocks that are not expected to persist in future earnings affect the numerator of the EP ratio. After controlling for these factors, we find that EP ratios for LIFO firms are actually lower than those of non‐LIFO firms, a result consistent with economic intuition and the result expected by Lee.